Ontological (In)Security and Neoliberal Governmentality: Explaining Australia's China Emergency. (23rd December 2021) - Pan, Chengxin; Hagström, Linus
Abstract : One of the mysteries in contemporary world politics is why in recent years Australia has been leading the world in its hawkish approach to China, its largest trading partner. More than most of its allies, the Australian government seems to regard the China emergency — fuelled by threat perceptions ranging from foreign influence operations to economic coercion — as more pressing than, say, climate change. This article extends and supplants existing explanations of this puzzle by providing a more theoretically oriented account. Situating Australia's China emergency in the context of its ontological (in)security, this article traces the rise of such insecurities and Australia's responses through the conceptual frameworks of state transformation and neoliberal governmentality, which together offer a more socially and historically grounded account of the dynamics of ontological (in)security. The article argues that the China emergency narrative, as a specific routinised form of neoliberal governmentality, both helps sustain Australia's dominant identity construction as a free, democratic, and resilient state, and provides a raison d'être for the national security state that has become part and parcel of the evolving techniques of neoliberal governmentality.